Co3O4-decorated hematite nanorods as an effective photoanode for solar water oxidation - Xi, Lifei (2012)
In this paper, we report a strategy to perform in-situ incorporation of oxygen evolution catalyst (OEC), Co3O4, during hydrothermal growth of Fe2O3 nanorod arrays. It was found that the highest photocurrent increase and onset potential shift was observed with 5% Co2+. The photocurrent density increases from 0.72 for the pristine Fe2O3 nanorod to 1.20 mA/cm2 at 1.23 V vs RHE (i.e. 67 % improvement) with 5 % Co2+ added. Concomitant with this improvement was a shift in the onset potential by about 40 mV and improvements in incident-photo-to-current-efficiencies (IPCE) and oxygen evolution. Hematite photoanodes with in-situ deposition of Co3O4 nanoparticles showed better performance than those prepared by ex-situ procedures because of high surface roughness, larger Co3O4/hematite interfacial area and smaller Co3O4 particle size.